Sagittal Plane Alignment and Functional Outcomes Following Surgery for Scheuermann Kyphosis - Vital,Luísa (2021)
Abstract Objective To evaluate and correlate the pelvic parameters, the sagittal balance (SB), and the functional outcome of the patients submitted to surgical treatment for Scheuermann hyperkyphosis (SK). Methods Patients submitted to surgery between January 2005 and December 2016 were included. The following radiographic measurements were obtained: thoracic kyphosis (TK); lumbar lordosis (LL); SB; pelvic incidence (PI); pelvic tilt (PT); and sacral slope (SS). Complications during the follow-up period were recorded. Results A total of 19 patients were included (16 males): the mean preoperative kyphosis was of 83°, and the postoperative kyphosis was of 57°. The mean preoperative lumbar lordosis was of 66°, with a postoperative spontaneous correction of 47°. Regarding the preoperative pelvic parameters, the average PI, PT and SS were of 48°,10° and 39° respectively. In the postoperative period, these values were of 50°, 16° and 35° respectively. The preoperative SB was neutral, and it was maintained after the surgical correction. Concerning complications during the follow-up period, three junctional kyphosis were observed–two requiring revision surgery, one nonunion, and one dehiscence of the surgical wound. Regarding the functional results, the average score on the Scoliosis Research Society-22 (SRS-22) patient questionnaire was of 4.04, and we verified that the SB obtained in the postoperative period had no influence on the functional outcome (p = 0.125) nor on the postoperative LL (p = 0.851). Conclusion We verified a spontaneous improvement in the lumbar hyperlordosis at levels not included in the fusion after correction of the TK. Although the postoperative functional results were globally high, we did not find any statistically significant relationship with TK nor LLs. high PI is associated with a greater rate of complications regarding the proximal junctional kyphosis (PJK), and these pelvic parameters should be considered at the time of the SK surgical treatment.